Metodologias interdisciplinares em estudos de geoconservação de património geológico-mineiro : o caso da antiga mina de volfrâmio das Aveleiras (Mire de Tibães) : the case of ancient Aveleiras wolfram mine (Mire de Tibães) - Lopes, Maria Eugénia Oliveira (2008)
This work emphasizes the importance of recovery processes of abandoned mining heritage, as an example of the transformative process of an organization towards a second life cycle. This perspective reflects an important measure for sustainability, either for the organization and the surrounding environment. The Aveleira Mine is an old wolfram mine, belonging to the Monastery of St Martin of Tibães, near Braga, in the North of Portugal. It was the mother house of the Benedictine order in Portugal. By the initiative of the Tibães Monastery this mine will probably reconverted, partially, in a geosite and, probably, near future in mining museum. The work aim was to present a methodological approach, in a geoconservation point of view, allowing an ulterior partially recovering and stabilization of the Aveleiras ancient mine.